Adaptation of Coastal Adolescents to Digital Technology in Improving Health Behavior - Diah Wijayanti Sutha; Nathratul Ayeshah Binti Zulkifli; Christine Christine; Siti Novianti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Digital technology increasingly shapes adolescent health behavior; however, little is known about how adolescents in remote coastal communities adapt to digital health information environments. This study aims to explore how digital technology influences adolescent health behaviors and how environmental and social factors shape adolescents’ adaptation to digital technology in a coastal community. This qualitative study employed a phenomenological approach. Data were collected through in-depth interviews with 27 adolescents aged 15–19 years and two focus group discussions conducted in Mandangin Island, Madura, Indonesia. Participants were selected using purposive sampling based on their access to digital devices and internet connectivity. Data were analyzed using thematic analysis supported by NVivo 12 software. Digital technology, particularly social media platforms such as TikTok, Instagram, and YouTube, emerged as the primary source of health information for adolescents. Participants reported increased awareness of healthy behaviors, including diet, physical activity, and mental well-being. However, significant challenges were identified, including limited internet access, unequal device ownership, and difficulties in distinguishing credible information from misinformation. Peer influence played a central role in shaping how adolescents adopt and interpret online health information. Digital technology has the potential to support positive health behavior among adolescents in coastal communities. Nevertheless, digital inequality and limited digital health literacy restrict its effectiveness. Strengthening digital literacy and improving equitable access to technology are essential to optimize digital health interventions for adolescents in underserved coastal areas Keywords: Adolescent Health, Digital Health Literacy, Health Behavior, Digital Divide, Coastal Community, Qualitative Research